Surgical outcome of temporal plus epilepsy is improved by multilobar resection. Issue 4 (15th February 2022) - Barba, Carmen; Rheims, Sylvain; Minotti, Lorella; Grisotto, Laura; Chabardès, Stéphan; Guenot, Marc; Isnard, Jean; Pellacani, Simona; Hermier, Marc; Ryvlin, Philippe; Kahane, Philippe
Abstract: Objective: Temporal plus epilepsy (TPE) represents a rare type of epilepsy characterized by a complex epileptogenic zone including the temporal lobe and the close neighboring structures. We investigated whether the complete resection of temporal plus epileptogenic zone as defined through stereoelectroencephalography (SEEG) might improve seizure outcome in 38 patients with TPE. Methods: Inclusion criteria were as follows: epilepsy surgery performed between January 1990 and December 2001, SEEG defining a temporal plus epileptogenic zone, unilobar temporal operations ("temporal lobe epilepsy [TLE] surgery") or multilobar interventions including the temporal lobe ("TPE surgery"), magnetic resonance imaging either normal or showing signs of hippocampal sclerosis, and postoperative follow‐up of at least 12 months. For each assessment of postoperative seizure outcome, at 1, 2, 5, and 10 years, we carried out descriptive analysis and classical tests of hypothesis, namely, Pearson χ 2 test or Fisher exact test of independence on tables of frequency for each categorical variable of interest and Student t ‐test for each continuous variable of interest, when appropriate. Results: Twenty‐one patients underwent TPE surgery and 17 underwent TLE surgery with a follow‐up of 12.4 ± 8.16 years. In the multivariate models, there was a significant effect of the time from surgery on Engel Class IA versus IB–IV outcome, with a steadily worsening trend from 5‐year follow‐up onward. TPE surgery was associated with better results than TLE surgery. Significance: This study suggests that surgical outcome in patients with TPE can be improved by a tailored, multilobar resection and confirms that SEEG is mandatory when a TPE is suspected.